Function of Individual 30S Subunit Proteins of Escherichia coli. Effect of Specific Immunoglobulin Fragments (Fab) on Activities of Ribosomal Decoding Sites - Lelong, J. C. (Proc Natl Acad Sci U S A, 1974)
Specific anti-30S protein immunoglobulin G fragments (Fab) were used to determine the contribution of each of the 30S ribosomal proteins to: (1) polyphenylalanine synthesis, (2) initiation factor-dependent binding of fMet-tRNA, (3) T-factor-dependent binding of phenylalanyl-tRNA, and (4) fixation of radioactive dihydrostreptomycin. Twenty of the 21 possible antibodies (antibody against S17 excepted) were used. In conditions where all the 30S proteins were accessible to Fabs, all of these monovalent antibodies strongly inhibited polyphenylalanine synthesis in vitro. Antibodies against S4, S6, S7, S12, S15, and S16, however, showed a weaker effect. 30S proteins can be classified into four categories by their contributions to the function of sites “A” and “P”: class I appears nonessential for tRNA positioning at either site (S4, S7, S15, and S16); class II includes proteins whose role in initiation is critical (S2, S5, S6, S12, and S13); class III (S8, S9, S11, and S18) corresponds to proteins whose blockade prevents internal (elongation factor Tudependent) positioning; and class IV includes entities that are essential for activities of both “A” and “P” sites (S1, S3, S10, S14, S19, S20, and S21). Dihydrostreptomycin fixation to the 30S or 70S ribosomes was inhibited by antibodies against S1, S10, S11, S18, S19, S20, and S21, but only weakly by the anti-S12 (Str A protein) Fab. The significance of these results is discussed in relation to 30S protein function, heterogeneity, and topography.